2018
DOI: 10.2147/ndt.s172886
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of chromosome Y loss in men with schizophrenia

Abstract: BackgroundLife expectancy is 10–20 years lower in patients with schizophrenia than in the general population. In addition, men with schizophrenia have an earlier age at onset, more pronounced deficit symptoms, poorer course, and poorer response to antipsychotic medications than women. Recent studies have indicated that loss of chromosome Y (LOY) in peripheral blood is associated with an increased risk of all-cause mortality. In order to elucidate the pathophysiology of male-specific features, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…In this study, acute myeloid leukaemia patients exhibited Y chromosome hypoploidy in the bone marrow [Holmes et al, 1985]. Since then, several reports demonstrated an potential association between LOY and the development of diseases such as Alzheimer, cardiovascular events, autoimmune diseases, and a wide number of cancers [Holmes et al, 1985;Castedo et al, 1992;Hunter et al, 1993;Guttenbach et al, 1995;Sauter et al, 1995;Brunelli et al, 2003;Gilgenkrantz, 2008;Klatte et al, 2009;Persani et al, 2012;Lleo et al, 2013;Dumanski et al, 2016;Noveski et al, 2016;Forsberg, 2017;Forsberg et al, 2017;Haitjema et al, 2017;Hirata et al, 2018]. Furthermore, Arseneault et al…”
Section: Loss Of Chromosome Ymentioning
confidence: 51%
See 3 more Smart Citations
“…In this study, acute myeloid leukaemia patients exhibited Y chromosome hypoploidy in the bone marrow [Holmes et al, 1985]. Since then, several reports demonstrated an potential association between LOY and the development of diseases such as Alzheimer, cardiovascular events, autoimmune diseases, and a wide number of cancers [Holmes et al, 1985;Castedo et al, 1992;Hunter et al, 1993;Guttenbach et al, 1995;Sauter et al, 1995;Brunelli et al, 2003;Gilgenkrantz, 2008;Klatte et al, 2009;Persani et al, 2012;Lleo et al, 2013;Dumanski et al, 2016;Noveski et al, 2016;Forsberg, 2017;Forsberg et al, 2017;Haitjema et al, 2017;Hirata et al, 2018]. Furthermore, Arseneault et al…”
Section: Loss Of Chromosome Ymentioning
confidence: 51%
“…Alternative to the expensiveness of the previously mentioned methods, and the increased amount of data that need to be interpreted in SNP-arrays and WGS, PCRbased methods can be a better standardization option. For example, several studies have used a Y/X ratio to detect LOY [Noveski et al, 2016;Hirata et al, 2018;Kimura et al, 2018]. Multiplex quantitative fluorescent-PCR amplifies the 2 AMEL fragments that are on both the X and Y chromosomes.…”
Section: Loy As a Biomarkermentioning
confidence: 99%
See 2 more Smart Citations
“…For over 50 years it has been known that LOY is a frequent event in cells of the hematopoietic system(2) and LOY in leukocytes was long viewed as a neutral event related to normal aging without phenotypical consequences(3). However, recent studies suggest the opposite as LOY has been found to be associated with increased risk for all-cause mortality(4, 5) as well as a growing list of diverse diseases and outcomes such as various forms of cancer(4, 6-9), autoimmune conditions(10, 11), Alzheimer’s disease(12), major cardiovascular events(13, 14), suicide completion(15), schizophrenia(16), diabetes(14) as well as age-related macular degeneration (AMD)(17).…”
Section: Introductionmentioning
confidence: 99%